Internalisasi Nilai Tolong-Menolong (Ta’awun) Melalui Video Ceramah Ustadz Abdul Somad Di Youtube - Rajaib; M. Ridho Alfarizi; Aisyah Tsabitah; Lala Arleka; Aki Pranoto; M. Ilham Pratama; Ibnu Rozali (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2026)
This study analyzes how the value of mutual assistance (ta’awun) is internalized through the YouTube sermon of Abdul Somad. The research used a qualitative approach with content analysis methods. Primary data were taken from the sermon video entitled “LIVE | Tolong Menolong dan Kewajiban Sosial Dari Saling Peduli Ke Aksi Nyata | Ustadz Abdul Somad” uploaded on the official YouTube channel Ustadz Abdul Somad Official. Secondary data came from audience comments and live chats. Data were collected through online observation and documentation, then analyzed using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. The findings show that Ustaz Abdul Somad delivers the value of ta’awun through a contextual da’wah approach that connects Islamic teachings with current social issues. The internalization process occurs through cognitive, affective, and behavioral stages, supported by YouTube’s interactive features. These interactions encourage digital solidarity and charitable practices among viewers. The study concludes that ta’awun remains highly relevant in responding to individualism and declining empathy in digital society. Thus, YouTube serves not only as a da’wah platform but also as a medium for strengthening social awareness, solidarity, and concern in contemporary Muslim society.